The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1021/ic301645j
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Zinc Coordination in Human Carbonic Anhydrase II

Abstract: Carbonic anhydrase (CA) is a well-studied, zinc-dependent metalloenzyme that catalyzes the hydrolysis of carbon dioxide to the bicarbonate ion. The apo-form of CA (apoCA) is relatively easy to generate, and the reconstitution of the human erythrocyte CA has been initially investigated. In the past, these studies have continually relied on equilibrium dialysis measurements to ascertain an extremely strong association constant (Ka ~ 1.2×1012) for Zn2+. However, new reactivity data and isothermal titration calori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 41 publications
(98 reference statements)
3
54
0
3
Order By: Relevance
“…Since ligand pKa values are not known, the total number of protons that are displaced upon metal binding (a + 2b in Scheme 1) cannot be calculated using the approach described above. An alternate method [73,74], which takes advantage of the change in ΔH HB if the experimental buffer is altered, has been widely used in ITC experiments [4,10,11,24,26,41,75]. Practically, this strategy requires multiple titrations to be carried out at the same pH in at least three different buffers under otherwise identical experimental conditions.…”
Section: Metal-protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ligand pKa values are not known, the total number of protons that are displaced upon metal binding (a + 2b in Scheme 1) cannot be calculated using the approach described above. An alternate method [73,74], which takes advantage of the change in ΔH HB if the experimental buffer is altered, has been widely used in ITC experiments [4,10,11,24,26,41,75]. Practically, this strategy requires multiple titrations to be carried out at the same pH in at least three different buffers under otherwise identical experimental conditions.…”
Section: Metal-protein Interactionsmentioning
confidence: 99%
“…As such, only indirect experiments that rely on competition with another metal ion or spectroscopic probe can be used to investigate Zn 2+ -protein interactions. Alternatively, Zn 2+ binding events are characterized by a quantifiable heat signature which can be exploited by ITC to gain insight into Zn 2 + -dependent systems such as zinc finger domains [4][5][6][7], carbonic anhydrase [8][9][10], and insulin [11]. Additionally, ITC has played a role in understanding countless important bioinorganic systems including ferritin and transferrin [12][13][14][15][16][17], amyloid beta [18,19], nucleases [20][21][22][23] and cardiac troponin C [24].…”
Section: Introductionmentioning
confidence: 99%
“…These affinities are weaker than that of CAII measured by equilibrium dialysis (K d = 0.8 ± 0.1 pM); [16] however, recent isothermal titration calorimetry experiments suggest a three-orders of magnitude weaker affinity for CAII (K d = 0.45 nM). [17] Based on this newer measurement, α 3 DH 3 has an affinity only two-orders of magnitude weaker than CAII and stronger than those observed for our previously published Hg(II) S Zn(II) N (TRIL9CL23H) 3 (K d = 0.8 ± 0.1 and 0.22 ± 0.06 μM at pH 7.5 and 9.0, respectively). [18] A sample of Zn(II)α 3 DH 3 at pH 9.0 was analyzed by extended x-ray absorption fine structure (EXAFS) spectroscopy.…”
mentioning
confidence: 49%
“…These parameters are very similar to EXAFS distances measured for CAII (Zn-N/O of 1.98 Å). [17] The true indication of a successfully designed metalloenzyme mimic is catalytic activity toward the physiological reaction of the natural enzyme, in this case, the hydration of CO 2 . Using Khalif's [19] stopped flow indicator technique, Zn(II)α 3 DH 3 was found to be an efficient catalyst with activities that increase with pH (Table 2).…”
mentioning
confidence: 99%
“…Human carbonic anhydrase II is one of the most efficient enzymes (approaching the diffusion limit) which catalyzes the reversible interconversion between CO 2 and HCO 3 −. [56] Even though the mechanism, structure, and inhibition have been previously studied, de novo protein design still offers a novel approach to study and replicate an important function of a native metalloenzyme in a simplified peptide system. We have previously demonstrated a carbonic anhydrase model in a bimetallic 3SCC construct [Hg(II)] S [Zn(II)(H 2 O/OH − )] N (TRIL9CL23H) 3 n + and Zastrow et al reported this model to be within 500-fold of the fastest isozyme (CAII), which is the fastest CA model to date (Figure 2a).…”
Section: Functionalizing α3d Frameworkmentioning
confidence: 99%